Full life tables for South Africa from vital registration data, 2006-2008 - Marandu, Simon Hlomayi (Centre for Actuarial Research (CARE), 2015)
This research derives a set of full life tables for South Africa as a whole and by population group using vital registration data for the period 2006-2008. Given that not all deaths are registered, the research assesses the level of completeness of death registration for the national population and for all the population groups separately by using the deaths distribution methods.